Diversity of Harbinger-like Transposons in Teleost Fish Genomes - Ema Etchegaray; Corentin Dechaud; Jérémy Barbier; Magali Naville; Jean-Nicolas Volff (Animals, 2022)
Harbinger elements are DNA transposons that are widespread from plants to vertebrates but absent from mammalian genomes. Among vertebrates, teleost fish are the clade presenting not only the largest number of species but also the highest diversity of transposable elements, both quantitatively and qualitatively, making them a very attractive group to investigate the evolution of mobile sequences. We studied Harbinger DNA transposons and the distantly related ISL2EU elements in fish, focusing on representative teleost species compared to the spotted gar, the coelacanth, the elephant shark and the amphioxus. We observed high variability in the genomic composition of Harbinger-like sequences in teleost fish, as they covered 0.002–0.14% of the genome, when present. While Harbinger transposons might have been present in a common ancestor of all the fish species studied here, with secondary loss in elephant shark, our results suggests that ISL2EU elements were gained by horizontal transfer at the base of teleost fish 200–300 million years ago, and that there was secondary loss in a common ancestor of pufferfishes and stickleback. Harbinger transposons code for a transposase and a Myb-like protein. We reconstructed and compared molecular phylogenies of both proteins to get insights into the evolution of Harbinger transposons in fish. Transposase and Myb-like protein phylogenies showed global congruent evolution, indicating unique origin of the association between both genes and suggesting rare recombination between transposon sublineages. Finally, we report one case of Harbinger horizontal transfer between divergent fish species and the transcriptional activity of both Harbinger and ISL2EU transposons in teleost fish. There was male-biased expression in the gonads of the medaka fish.